Sociodemographic determinants of university students’ lifestyles (2014)
Objective It has been observed during recent decades that a large percentage of the population has an inadequate lifestyle and that there is a need for identifying factors determining such behavior pattern. This study was thus aimed at determining the association between lifestyle and sociodemographic variables of freshmen attending a state university in southern Brazil.Methods The sample consisted of 716 students (59.6 % female). The Fantastic questionnaire was used for evaluating the students’ lifestyles; their lifestyle was classified as being suitable or inadequate. The sociodemographic variables of interest were gender, age group ( and lt;20 and ≥20 years), paid work (yes or no), maternal education (≤4 years of study, 5-8 years and ≥9 years), study shift (daytime or night-time) and marital status (single and married). Binary logistic regression was used for determining associations between lifestyle and sociodemographic characteristics (p and lt;0.05 being significant).Results Inadequate lifestyle prevalence was 5.3 %. Adjusted analysis results indicated that students over 20 years-old (OR=2.87: 1.37-6.03 95 %CI) whose mothers’ formal education had lasted less than nine years (OR=2.23: 1.29-3.88 95 %CI) had a higher risk of having an inadequate lifestyle.Conclusion These findings may be useful for developing university healthcare promotion programs, paying special attention to older freshmen whose mothers have had less formal education.